An Immersed Boundary Method OpenFOAM Solver for Structure - Two-phase Flow Interaction - Do, Vu Q.; Nguyen, Bac Viet; Nguyen, Phu-Khanh; Pham, Van-Sang (Old Journal, 2019)
In this study, a numerical solver has been developed for simulating the interaction of solid bodies with two-phase flow. The simplified direct forcing method is adopted to describe the presence of structures in flow, combining with the Pressure-Implicit Split-Operator (PISO) algorithm to address the velocity-pressure coupling in Navier-Stokes equations. The fluid-fluid interface reconstruction is performed by an advanced free-surface capturing model based on the volume-of-fluid (VOF) model, thus higher interface resolution can be achieved without the need of other special treatment. The computational mesh is distributed more efficiently and economically at the interested regions, e.g. fluid-fluid interface/solid-fluid interfaces, through an adaptive mesh refinement process, which significantly reduces computation time, while maintains excellent accuracy, demonstrated by simulation results involving surface breakup, water impact, and bodies – free surface interaction.